Cold plasma: Microbial inactivation and effects on quality attributes of fresh and minimally processed fruits and Ready-To-Eat vegetables. (October 2021) - Mao, Lili; Mhaske, Pranita; Zing, Xin; Kasapis, Stefan; Majzoobi, Mahsa; Farahnaky, Asgar
Abstract: Background: Due to the increasing consumer awareness and rapidly changing lifestyle, there has been an exponential increase in the demand for healthy, fresh, minimally processed and Ready-To-Eat food products, especially fresh fruits and vegetables globally. These products though convenient, nutritious, and preferred as healthy alternatives, are also a source of increasing foodborne outbreaks due to their minimal processing marked with insufficient decontamination and preservation. Scope and approach: Recent literature was reviewed through search engines and scholarly journals in the areas of food processing and engineering and other related areas. The focus was on the papers published over the last 10 years. Key findings and conclusions: The efficacy of cold plasma as a mild, yet effective non thermal technique in inactivating pathogenic microorganisms while maintaining the quality of fresh and minimally processed fruits and vegetables and extending their shelf life is summarized and reviewed. Cold plasma is capable of producing safe fresh fruits and vegetables. The efficiency of the technique depends on product surface properties and several processing parameters that needs be optimized to achieve desirable results. Further research is needed to fine tune and streamline cold plasma processing in order to have a widespread industrial application for safe fresh and minimally processed fruits and Ready-To-Eat vegetables. Future research would focus on expanding industrial applications of cold plasma technology through product safety as well as designing and modeling universal plasma application systems capable of processing different fruits and vegetables without requiring time consuming set up trials. Highlights: CP is a promising non-thermal technology for producing fresh fruits and vegetables. CP reduces microbial load of fresh fruits and vegetables substantially. Efficacy of CP is significantly affected by shape and surface properties. New cold plasma systems require novel and smart engineering designs.